INDONESIAN CONSTITUTIONAL LAW, THE CONSTITUTION IN ISLAMIC LAW, AND CONSTITUTIONALISM - Asasriwarni, Asasriwarni; Matondang, Ikhwan; Ali, Azizah (Hukum tata Negara/Siyasah, 2025)
In governing the state, government, and society through legal norms in the Republic of Indonesia, Pancasila is a fundamental norm. The 1945 Constitution of the Republic of Indonesia has undergone four stages of change throughout history, namely the 1945 Constitution, the process of constitutional change in Indonesia's history, and several instances where political forces have been used to interpret it. Both work together to create a good governance system that benefits all citizens. Therefore, a grand design must be formulated to ensure that legislation has a clear direction and accelerates the realization of a welfare state. Policies determine the legal rules that should apply in various aspects of social and state life. The research objective is to understand the existence of law and power to regulate life as the foundational principle of the state. The method used is a normative research approach through a historical perspective, employing library research. Indonesia is not a country that fully adheres to Islamic law, but it is a legal state where all policies, whether currently in effect or future, are based on law. The abundance of positive law influenced by Islamic law is partly due to Indonesia having the largest Muslim population in the world.